Марія Грінченко в історії української фольклористики - Козар, Л. (Народна творчість та етнографія, 2005)
This article concentrates attention of the readers on the role of Maria Hrinchenko in the development of the Ukrainian folkloristic of the end of the 19th-beginning of the 20th century. Maria Hrynchenko is famous folk texts collector (more then a 100 of the texts which she collected were published). She also was an editor of the proverbs anthology (more then 12000 samples and additional versions and variants) and the author of the research and memours on O.Markovych, L.Hlibov, I.Franko, B.Hrinchenko and others. Her work was highly appreciated by different scholars and cultural activists. Thus, Maria Hrinchenko deservs a special place in the history of Ukrainian folkloristic of the end of the 19th-beginning of the 20th century.